2020
DOI: 10.28982/josam.748864
|View full text |Cite
|
Sign up to set email alerts
|

Association of Borna disease virus with autism spectrum disorder in Turkish children

Abstract: Aim: Autism spectrum disorders are lifelong neurodevelopmental disorders whose pathogeneses are not fully understood. Borna disease virus is a neurotropic virus that affects the central nervous system. Considering the neuropsychiatric and behavioral effects of the virus, it can be suggested that it may play a role in autism spectrum disorder. However, there are insufficient evidence to support this. In this study, we aimed to investigate the presence of Borna disease virus in patients with autism spectrum diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Of the aforementioned studies, four reported on the seroprevalence for anti-BoDV-1 immunoglobulins [ 49 , 50 , 51 , 67 ]. All of these were performed by means of enzyme-linked immunoassay (ELISA), but significant heterogeneities were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the aforementioned studies, four reported on the seroprevalence for anti-BoDV-1 immunoglobulins [ 49 , 50 , 51 , 67 ]. All of these were performed by means of enzyme-linked immunoassay (ELISA), but significant heterogeneities were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The study from Özcan et al also relied on a homemade ELISA [ 50 , 70 ], which was obtained through a different strategy, and which only targeted p40 antigen. On the contrary, in the study by Yildirim et al [ 49 ], a commercial kit (Abbexa) was applied using precoated polyclonal anti-BoDV-1 IgG to detect antigens. Nothing was provided about the test protocol and the targeted antigens.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations